Initial results of the National Colorectal Cancer Screening Program in Lithuania. Issue 2 (March 2015) - Poskus, Tomas; Strupas, Kestutis; Mikalauskas, Saulius; Bitinaitė, Dominyka; Kavaliauskas, Augustas; Samalavicius, Narimantas E.; Saladzinskas, Zilvinas
<x xml:space="preserve">Abstract</x> The aim of the present study was to review the National Colorectal Cancer Screening Program (the Program) in Lithuania according to the criteria set by the European Union. In Lithuania, screening services are provided free of charge to the population. The National Health Insurance Fund (NHIF) reimburses the institutions for performing each service; each procedure within the Program has its own administrative code. All the information about the performance of the Program is collected in one institution – the NHIF. The results of the Program were retrieved from the database of NHIF from the start of the Program from 1 July 2009 to 1 July 2012. Descriptive analysis of epidemiological indicators was carried out. Results were compared with the references in the guidelines of the European Union for quality assurance in colorectal cancer (CRC) screening and diagnosis. Information service [which involves fecal immunochemical test (FIT)] was provided to 271 396 of 890 309 50–74-year-old residents. The screening uptake was 46.0% over 3 years. During this period, 19 455 (7.2%) FITs were positive and 251 941 (92.8%) FITs were negative. Referral for colonoscopy was performed in 10 190 (52.4%) patients. Colonoscopy was performed in 12 864 (66.1%) patients. Colonoscopy did not indicate any pathological findings in 8613 (67.0%) patients. Biopsies were performed in 4251 (33.0%) patients. The rate of high-grade neoplasia reported by pathologists was 3.9%; the rate of cancer was 3.1% of all colonoscopies. The rate of CRC detected by the Program was 0.2%. The CRC screening program in Lithuania meets most of the requirements for standardized CRC screening programs. The invitation coverage and rate of referral for colonoscopy after positive FIT should be improved.